Pendampingan Pembuatan Bahan Ajar Atraktif Bagi Tenaga Pengajar Sebagai Penunjang Pembelajaran Siswa/Siswi SMA BP FAI UMJ Muhammadiyah Boarding School "Ki Bagus Hadikusumo" - Zackharia Rialmi; Fitri Wahyuni; Ferdyanto Ferdyanto (Indonesian Journal of Society Engagement, 2021)
The use of technology in education is a necessity that cannot be avoided. Information technology-based learning such as presentations using Microsoft Power Point is an interesting process for students. Teaching materials/materials delivered using Microsoft power point can help students understand the material being taught. Generation Z as a generation that is already familiar with technological advances, of course, is also familiar with this technology. This affects their learning process. Visual learning style by relying on visual acuity is a mainstay for generation Z in the learning process. Attractive media and teaching materials will help them understand the material being studied. High school students BP FAI UMJ Muhammadiyah Boarding School (MBS) "Ki Bagus Hadikusumo" are included in generation Z who like visual learning styles. Therefore, the teaching staff of SMA BP FAI UMJ Muhammadiyah Boarding School (MBS) "Ki Bagus Hadikusumo" needs to deepen the use of attractive learning media in delivering material so that students more easily understand the subject. In this mentoring activity, it is expected that the teaching staff can explore the features in Microsoft Power Point so that they can create attractive teaching materials that can be implemented in the teaching and learning process in class or online.